ABSTRACT CONTROL OF CONSTITUTIONALITY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This work consists of a research about the autonomy of abstract control, by virtue of its objective nature. In this sense, the intended objective is the discussion regarding the subsistence of the scientific autonomy of the abstract control of constitutionality and investigates its application by the Supreme Court. The abstract normative inspection aims at protecting the constitutional order, not being linked to a juridical situation of individual or concrete character. Thus, it is not appropriate to use subjective norms to an objective process, because it would lead to the use of impertinent and consequently inappropriate procedural rules. Therefore, due to the specificity and consequent independence of the objective process, the existence of the scientific autonomy of the abstract review of constitutionality is verified. This is the understanding adopted by the Federal Supreme Court, as judged in the Right Share of Unconstitutionality n. 1.254/RJ, n. 3.345/DF and n. 2.422/DF. Therefore, through a deductive research, based on studies in the jurisprudence of the Federal Supreme Court, in the doctrine and in the Federal Constitution of 1988, this paper will support the thesis regarding the emancipation of constitutional procedural law abstract.